Pengaruh Motivasi Belajar dan Lingkungan Teman Sebaya Terhadap Prestasi Belajar Matematika Siswa - Wike Revanaliza; Tasnim Rahmat; Rusdi Rusdi; Haida Fitri (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study was to determine the significant effect of learning motivation on mathematics learning achievement of 7th grade students of SMPN 7 Bukittinggi and to determine the significant effect of peer environment on mathematics learning achievement of 7th grade students of SMPN 7 Bukittinggi. The population of this study was 226 people and the sample was 34 people. The instruments used in this study were a learning motivation questionnaire and a peer environment questionnaire. The data analysis technique used is regression test. From the results of this study, the regression equation for learning motivation on learning achievement is Y = 4.88038462 + 0.44717308X1 with a correlation coefficient value of 0.60809407 which indicates a strong relationship strength and a determinant coefficient of 36.97%. Furthermore, from the regression significance test obtained > so, can be concluded that there is a significant influence of learning motivation on learning achievement in mathematics. Furthermore, from the peer environment regression equation on learning achievement, Y = 2.800158944+0.57757672 X2 with a correlation coefficient value of 0.45598425 which indicates a moderate relationship strength and a determinant coefficient of 20.79%. The results of the regression significance test, it was obtained that > so, can be concluded that there is a significant influence of peer environment on learning achievement in mathematic.